1997
DOI: 10.1016/s0029-7844(97)00214-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of instituting an elective labor epidural program on the operative delivery rate

Abstract: Our study demonstrated no increase in the rate of operative deliveries in a population that suddenly received access to on-request labor epidurals. We believe this option should be offered to parturients without making them feel that they must choose between comfort and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 16 publications
1
8
1
Order By: Relevance
“…The high rate of epidural use in our population is consistent with other studies, which have shown that most United States women electively receive epidural analgesia when it is easily available 24 hours a day ( 10). Our 78 percent rate of epidural use was even higher than the 51 percent rate reported in a national survey of hospitals with more than 1500 deliveries per year ( 4).…”
Section: Discussionsupporting
confidence: 91%
“…The high rate of epidural use in our population is consistent with other studies, which have shown that most United States women electively receive epidural analgesia when it is easily available 24 hours a day ( 10). Our 78 percent rate of epidural use was even higher than the 51 percent rate reported in a national survey of hospitals with more than 1500 deliveries per year ( 4).…”
Section: Discussionsupporting
confidence: 91%
“…[27][28][29] Observational studies show that sudden large changes in epidural utilization are not associated with alterations in hospital-wide cesarean delivery rates. This has been demonstrated in urban 30 and rural 31,32 hospitals, in academic 30 and community 31,32 practices, and with military, 33 lower-class, 30,32 and middle-class 31 patient populations. Despite the stability of the hospitals' cesarean delivery rates, if one examines the patient subgroups with free access to epidural analgesia, the dystocia cesarean delivery rate is 2 to 8 times higher among patients who choose epidural analgesia.…”
Section: Commentmentioning
confidence: 88%
“…Despite the stability of the hospitals' cesarean delivery rates, if one examines the patient subgroups with free access to epidural analgesia, the dystocia cesarean delivery rate is 2 to 8 times higher among patients who choose epidural analgesia. 30,31,33 Factors leading to dystocia increase labor pain and epidural utilization. 3,22 Therefore, studies not grouping patients by intent to treat will be biased toward an increased cesarean delivery rate among patients requesting epidural analgesia.…”
Section: Commentmentioning
confidence: 99%
“…23 A conservative approach to epidural analgesia has in the past been adopted by the obstetrics team, due to concerns about the possibility of an increased incidence of assisted deliveries, 5 a prolonged second stage of labour (as was shown in retrospective studies 24,25 ), and the incorrect belief that Caesarean section rates increased. [11][12][13][26][27][28][29][30] Further major limitations to expansion of the service at TBH have included constraints on anaesthetic and nursing human resources, and inadequate education of the nursing staff, which limits our epidural service to 45 h per week. In this context, it is our opinion that four epidurals per day would be safe and manageable.…”
Section: Discussionmentioning
confidence: 99%